From Fang to Fatality: A Rare Case of Intracranial Bleed after Snakebite - M. Yashwanth (APIK Journal of Internal Medicine, 2026)
Abstract Snakebite envenomation is a significant public health concern in tropical countries such as India. Although coagulopathy and local tissue necrosis are common complications, intracranial hemorrhage (ICH) remains a rare but life-threatening manifestation. We report a case of a 45-year-old male who developed fatal ICH after a viper bite, underscoring the importance of early recognition and management of this rare complication.